In vitro and in vivo effects of insulin-producing cells generated by xeno-antigen free 3D culture with RCP piece - Tetsuya Ikemoto (Nature Portfolio, 2019)
Abstract To establish widespread cell therapy for type 1 diabetes mellitus, we aimed to develop an effective protocol for generating insulin-producing cells (IPCs) from adipose-derived stem cells (ADSCs). We established a 3D culture using a human recombinant peptide (RCP) petaloid μ-piece with xeno-antigen free reagents. Briefly, we employed our two-step protocol to differentiate ADSCs in 96-well dishes and cultured cells in xeno-antigen free reagents with 0.1 mg/mL RCP μ-piece for 7 days (step 1), followed by addition of histone deacetylase inhibitor for 14 days (step 2). Generated IPCs were strongly stained with dithizone, anti-insulin antibody at day 21, and microstructures resembling insulin secretory granules were detected by electron microscopy. Glucose stimulation index (maximum value, 4.9) and MAFA mRNA expression were significantly higher in 3D cultured cells compared with conventionally cultured cells (P < 0.01 and P < 0.05, respectively). The hyperglycaemic state of streptozotocin-induced diabetic nude mice converted to normoglycaemic state around 14 days after transplantation of 96 IPCs under kidney capsule or intra-mesentery. Histological evaluation revealed that insulin and C-peptide positive structures existed at day 120. Our established xeno-antigen free and RCP petaloid μ-piece 3D culture method for generating IPCs may be suitable for clinical application, due to the proven effectiveness in vitro and in vivo.